2008
DOI: 10.1007/s00701-008-0166-4
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife surgery of large meningiomas: early response to treatment

Abstract: It is suggested on the basis of this material that the dosimetry used here permits the safe Gamma Knife treatment of larger meningiomas within the range reported. The early radiological response is encouraging, but further follow-up is needed to check long term tumour control. A qualitative method of tumour volume assessment is presented. It seems to be a simpler and more reliable way of assessing tumour volume changes than other methods currently in routine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 51 publications
2
29
1
4
Order By: Relevance
“…29 Other studies, including one from the University of Pittsburgh, have found that tumor volume greater than 8 cm 3 was the most important parameter associated with a worse prognosis for radiosurgery of benign meningiomas. 8,15,16,20 From 1989 through 2012, our Gamma Knife center treated 75 patients with meningiomas at least 8 cm 3 in volume at initial planning (mean preradiosurgical tumor volume = 14.1 cm 3 ). Forty percent of patients were treated with primary radiosurgery, and the remaining 60% were treated following resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Other studies, including one from the University of Pittsburgh, have found that tumor volume greater than 8 cm 3 was the most important parameter associated with a worse prognosis for radiosurgery of benign meningiomas. 8,15,16,20 From 1989 through 2012, our Gamma Knife center treated 75 patients with meningiomas at least 8 cm 3 in volume at initial planning (mean preradiosurgical tumor volume = 14.1 cm 3 ). Forty percent of patients were treated with primary radiosurgery, and the remaining 60% were treated following resection.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] In prior studies, large meningiomas have been treated with varying degrees of success, but radiosurgery outcomes appear to worsen for patients harboring meningiomas greater than 8 cm 3 in volume. 8,15,16,20,42 An 8-cm 3 volume corresponds to a lesion with an approximate diameter of 2.5 cm. Radiosurgery to lesions in excess of 8-cm 3 volume has been linked to worsening outcome with arteriovenous malformations, acoustic neuromas, and brain metastases as well.…”
mentioning
confidence: 99%
“…According to the literature, radiosurgical treatments for large‐volume tumors or AVMs may sustain a higher risk of complications, such as tumor swelling or brain edema 1, 2, 3, 10, 13. Ideally, a conformal and sufficient target dose should be maintained for effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, an increasing number of studies have shown that large intracranial lesions with a volume of 20–30 cm 3 can also be treated using GKRS 1, 2, 3, 4. Typically, multiple shots are required to cover target volumes (TVs) for treating large targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation